Gravity waves above the northern Atlantic and Europe during streamer events using Aeolus - S. Wüst; L. Küchelbacher; F. Trinkl; F. Trinkl; M. Bittner; M. Bittner (Atmospheric Measurement Techniques)
Information about the energy density of gravity waves (GWs) is crucial for improving atmosphere models. So far, most space-based studies report the potential energy, Epot, of GWs, as temperature measurements from satellites are more common.